RESEARCH ON THE PRESSURE SHELL STRUCTURAL STRENGTH CHARACTERISTIC OF MARINE DETECTOR - ZHANG Liang; LIU DaXing; CHEN YuLong (Jixie qiangdu, 2015)
Referring to the standard equipments and the classic design formulas,a structural style of the classic pressure shell is deduced by researching the structural strength of the non-standard equipments according to the design requirements. And the strength and the failure modes of the pressure shell are assessed by using the modified arc-length method to analyze the buckling instability. Considering the actual connective type of the pressure shell structure,the effect is analyzed that the head structural style makes on the pressure shell strength characteristic. Then,the research shows that the stability,the failure modes and the ultimate strength of the pressure shell have relationship with the contact radio of the head and the cylinder wall,and it can be known that the stability of the pressure shell can be effectively promoted by increasing the contact radio. When the contact radio is increased to a certain degree,the failure modes may be changed from the buckling failure to the yield failure.Meanwhile,the quasi-linear relationship is presented between the contact radio and the ultimate strength safety reserve factor,which the greater the contact radio and the higher the safety reserve factor.